Food safety impacts of antimicrobial use and their residues in aquaculture - Reuben Chukwuka Okocha; Isaac Olufemi Olatoye; Olufemi Bolarinwa Adedeji (Frontiers Media S.A., 2018)
Abstract Background Residues of antimicrobials in food have received much attention in recent years because of growing food safety and public health concerns. Their presence in food of animal origin constitutes socioeconomic challenges in international trade in animal and animal products. The major public health significances of antimicrobial residues include the development of antimicrobial drug resistance, hypersensitivity reaction, carcinogenicity, mutagenicity, teratogenicity, bone marrow depression, and disruption of normal intestinal flora. Indiscriminate use of antimicrobials in aquaculture resulting in occurrence of residues in aquaculture products and associated harmful health effects in humans requires control measures to ensure consumer protection. Main body This article focuses on factors contributing to the presence of antimicrobial residues in aquaculture products and their implications on consumers' safety. Regulatory actions aimed at prudent use of veterinary drugs in food-producing animals with emphasis on aquaculture for safe and wholesome food production are also reviewed. Conclusion Prudent use of antibiotics in aquaculture under veterinary supervision is critical in ensuring safety of aquaculture products. Good animal husbandry practices as well as the use of alternatives to antibiotics such as vaccination, probiotics, phage therapy, and essential oils are recommended panaceas to reducing the use of antimicrobial residues in aquaculture and consequent food safety effects.